2008
DOI: 10.1002/ibd.20277
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profiling during protection from colitis by regulatory T cells

Abstract: We suggest that these molecules alone or in combination could be future therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
2
13
1
Order By: Relevance
“…Although known primarily as a CCR5 antagonist, TAK-779 has also been shown to block CXCR3 in mice, but not in humans 4951 . Although CXCR3 expression has been described on Treg in some models of inflammation 62,63 , we did not observe expression of CXCR3 on Treg in our tumor-bearing mice (data not shown). Another compound, Met-CCL5, is a CCR1 and CCR5 antagonist 64 , which has been shown to inhibit the growth of murine breast carcinoma in vivo ; however, in this tumor model, there is little CD4 + lymphocytic infiltration 65 .…”
Section: Discussioncontrasting
confidence: 63%
“…Although known primarily as a CCR5 antagonist, TAK-779 has also been shown to block CXCR3 in mice, but not in humans 4951 . Although CXCR3 expression has been described on Treg in some models of inflammation 62,63 , we did not observe expression of CXCR3 on Treg in our tumor-bearing mice (data not shown). Another compound, Met-CCL5, is a CCR1 and CCR5 antagonist 64 , which has been shown to inhibit the growth of murine breast carcinoma in vivo ; however, in this tumor model, there is little CD4 + lymphocytic infiltration 65 .…”
Section: Discussioncontrasting
confidence: 63%
“…4). This is in agreement with a previous study where we found the expression of cxcl5 to be upregulated more than 50-fold in colitic animals, 23 thus indicating that this chemokine does play a very important role in induction and maintenance of colitis. The cytokine CXCL5 released by intestinal epithelial cells is known to recruit CXCR2-expressing neutrophils to the site of inflammation both in mouse and man.…”
Section: Discussionsupporting
confidence: 94%
“…These data reveal that the majority of differentially expressed genes during both DSS colitis and UC are upregulated, while a lesser number are downregulated. Interestingly, these data identify a greater number of similarly regulated genes than previously reported (41,29).…”
Section: Genome Profiling Of Experimental and Ulcerative Colitismentioning
confidence: 62%